The self-paced submaximal run test: associations with the graded exercise test and reliability - Sangan, H. F.; Hopker, J. G.; Davison, G.; McLaren, S. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To assess the reliability and construct validity of a self-paced, submaximal run test (SRTRPE) for monitoring aerobic fitness. The SRTRPE monitors running velocity (v), heart rate (HRex), and blood lactate concentration (B[La]), during three 3-minute stages prescribed by ratings of perceived exertion (RPEs) of 10, 13, and 17.